2008
DOI: 10.1200/jco.2007.13.5913
|View full text |Cite
|
Sign up to set email alerts
|

Review of Phase II Trial Designs Used in Studies of Molecular Targeted Agents: Outcomes and Predictors of Success in Phase III

Abstract: In practice, phase II design for targeted agents is similar to that for cytotoxics. Objective response seems to be a useful end point for screening new targeted agents because, in our review, its observation predicted for eventual success. Improvements in design are recommended, as is more frequent inclusion of biological questions as part of phase II trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 77 publications
1
85
0
Order By: Relevance
“…A recent review showed that a majority of phase II trials evaluating targeted agents are single-arm studies and that objective response rate (ORR), as used in most phase II trials evaluating chemotherapy, predicts (albeit imperfectly) eventual success in phase III trials (22). However, ORRs in most phase III RCTs were lower than those in preceding phase II studies, with a mean absolute difference of 12.9% (23).…”
Section: Early-phase Clinical Trialsmentioning
confidence: 90%
“…A recent review showed that a majority of phase II trials evaluating targeted agents are single-arm studies and that objective response rate (ORR), as used in most phase II trials evaluating chemotherapy, predicts (albeit imperfectly) eventual success in phase III trials (22). However, ORRs in most phase III RCTs were lower than those in preceding phase II studies, with a mean absolute difference of 12.9% (23).…”
Section: Early-phase Clinical Trialsmentioning
confidence: 90%
“…The quality of phase II data may be one of the most important factors for predicting the success of a phase III trial (7,8). However, many phase II trials prove to be of limited value in the drug development trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Objective response by sizebased decrease in tumor, may translate to an early clinical endpoint, in substitution for overall survival [18] . AntiVEGF therapy has primarily cytostatic effects, may prune and normalize the tumor vasculature, and can have substantial systemic effects such as modulation of circulating proangiogenic and proinflammatory cytokines and cells [1924] .…”
Section: Response Biomarkermentioning
confidence: 99%